Wage Statistics in the Twelfth Census - Abbott, Edith (Journal of Political Economy, 1904)
FOR the second time in the history of the federal census the statistics of wages have been made the subject of an exhaustive special report' prepared under the direction of an expert statistician. The publication of this volume marks an important point in the development of wage statistics in the United States, and it seems worth while to consider at some length certain questions regarding it: (i) How does the scope of the inquiry differ from that of previous census investigations into wages? (2) In what respect is the method of presentation and tabulation new, and what are the relative advantages or disadvantages of this method of treatment? (3) What conclusions are reached regarding the trend of wages during the decade? The one other census volume which gives a detailed presentation of wage statistics is the work of Mr. Joseph D. Weeks for the Tenth Census. Many of the data collected are for a period of fifty years, and while the scope is much broader than that of Professor Dewey's report, which presents returns only for i890 and i900, the latter is immeasurably superior in the completeness and accuracy of its statistics;2 and, indeed, it would be saying that there had been small progress in statistical method in the last twenty years if this were not so. Except for this work of Mr. Weeks, all wage statistics in the census up to the present time have been included in the Census of Manufactures, and in general their purpose has been to show the